2020
DOI: 10.1063/1.5143723
|View full text |Cite
|
Sign up to set email alerts
|

Physics of high-efficiency 240–260 nm deep-ultraviolet lasers and light-emitting diodes on AlGaN substrate

Abstract: High-efficiency III-nitride deep-ultraviolet (DUV) lasers and light-emitting diodes (LEDs) with emission wavelengths of 240–260 nm are extremely difficult to realize due to large defect density from III-nitride materials and existence of optical polarization crossover from conventional AlGaN-based quantum wells (QWs). Free-standing wurtzite AlGaN templates have been studied and developed recently; however, the physics and optical properties of AlGaN-based emitters on AlGaN templates are still relatively lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The mobility for electrons and holes are set as 300 cm 2 V −1 s −1 and 8 cm 2 V −1 s −1 respectively. The Auger coefficient is set as 5 × 10 −31 cm 6 s −1 whereas the SRH recombination lifetime is set as 10 ns which is in agreement with the previously reported values [27]. Further, the optical modal field confinement factors in the active region of LD are calculated for each mode.…”
Section: Device Modelling and Simulationmentioning
confidence: 54%
“…The mobility for electrons and holes are set as 300 cm 2 V −1 s −1 and 8 cm 2 V −1 s −1 respectively. The Auger coefficient is set as 5 × 10 −31 cm 6 s −1 whereas the SRH recombination lifetime is set as 10 ns which is in agreement with the previously reported values [27]. Further, the optical modal field confinement factors in the active region of LD are calculated for each mode.…”
Section: Device Modelling and Simulationmentioning
confidence: 54%
“…In 2006, Serkan Butun et al prepared and tested an AlGaN photodetector with MSM structure with Al component up to 0.75, which has met the requirements of solar blind ultraviolet detection [8]. Liu et al studied the optical properties and quantum efficiency of AlGaN quantum well on AlGaN and AlN, and found that the quantum well on AlGaN substrate has better optical gain, which indicates that AlGaN substrate has a broad application prospect in efficient deep ultraviolet lasers and light-emitting diodes [9]. Therefore, AlGaN semiconductor materials have a wide range of application prospects.…”
Section: Introductionmentioning
confidence: 99%